Performance of an Early Infant Diagnostic Test, AmpliSens DNA-HIV-FRT, Using Dried Blood Spots Collected from Children Born to Human Immunodeficiency Virus-Infected Mothers in Ukraine - Chang, Joy (J Clin Microbiol, 2015)
An accurate accessible test for early infant diagnosis (EID) is crucial for identifying HIV-infected infants and linking them to treatment. To improve EID services in Ukraine, dried blood spot (DBS) samples obtained from 237 HIV-exposed children (≤18 months of age) in six regions in Ukraine in 2012 to 2013 were tested with the AmpliSens DNA-HIV-FRT assay, the Roche COBAS AmpliPrep/COBAS TaqMan (CAP/CTM) HIV-1 Qual test, and the Abbott RealTime HIV-1 Qualitative assay. In comparison with the paired whole-blood results generated from AmpliSens testing at the oblast HIV reference laboratories in Ukraine, the sensitivity was 0.99 (95% confidence interval [CI], 0.95 to 1.00) for the AmpliSens and Roche CAP/CTM Qual assays and 0.96 (95% CI, 0.90 to 0.98) for the Abbott Qualitative assay. The specificity was 1.00 (95% CI, 0.97 to 1.00) for the AmpliSens and Abbott Qualitative assays and 0.99 (95% CI, 0.96 to 1.00) for the Roche CAP/CTM Qual assay. McNemar analysis indicated that the proportions of positive results for the tests were not significantly different (P > 0.05). Cohen's kappa (0.97 to 0.99) indicated almost perfect agreement among the three tests. These results indicated that the AmpliSens DBS and whole-blood tests performed equally well and were comparable to the two commercially available EID tests. More importantly, the performance characteristics of the AmpliSens DBS test meets the World Health Organization EID test requirements; implementing AmpliSens DBS testing might improve EID services in resource-limited settings.